The Ability Of Islamic Boarding School Students In Facing The Digital Literacy Era With Critical Reading - Anwar Hafidzi (Departement Of Master Of Islamic Education Graduate Programme Sultan Muhammad Syafiuddin Institute Of Islamic Studies Sambas, Indonesia, 2020)
Abstract: In order to develop information technology, the national education system must be improved, and Pondok Pesantren is no exception. Since the ratification of Islamic Boarding School Law there have been at least four key fields, including the eight aspects of digital-age literacy, core literacy, science, information, visuals, technology, multicultural awareness and global knowledge. The tool used in the present study was to develop the teaching abilities of Islamic boarding school students and to write them through a bibliography approach and approach to education through Kelvin Seifert's digital literacy techniques, opportunities and challenges. These findings show the students' ability to learn and comprehend it again with good analytics can be enhanced with the approach to classical book studies with critical thinking skills. Keywords: Ability; Digital-Age Literacy; Islamic education; boarding school; Abstrak: Untuk mengembangkan teknologi informasi, sistem pendidikan nasional harus diperbaiki, tidak terkecuali Pondok Pesantren. Sejak disahkannya UU Pesantren setidaknya terdapat empat bidang utama, yaitu delapan aspek literasi era digital, literasi inti, sains, informasi, visual, teknologi, kesadaran multikultural, dan pengetahuan global. Alat yang digunakan dalam penelitian ini adalah untuk mengembangkan kemampuan mengajar siswa pesantren dan menuliskannya melalui pendekatan bibliografi dan pendekatan pendidikan melalui teknik literasi digital, peluang dan tantangan Kelvin Seifert. Temuan ini menunjukkan kemampuan siswa untuk belajar dan memahaminya kembali dengan analitik yang baik dapat ditingkatkan dengan pendekatan studi buku klasik dengan kemampuan berpikir kritis. Kata kunci: Kemampuan; Literasi Era Digital; Pendidikan Islam; pesantren;